Stakeholder Perceptions and Experiences of a College Live Mascot Program: a Study of Higher Education Ad Hoc Change - Patterson, Clinton A. (Innov High Educ, 2021)
Organizational change is a complex and critical issue in higher education today. Changes experienced across institutional systems have both short-term and long-term impact, making this phenomenon ripe for educational leadership research. Many universities and colleges have applied Kotter’s (1995) eight-step change model prescriptively to implement academic initiatives, curriculum revisions, and strategic vision. However, Kotter’s (1995) model has not previously explored ad hoc changes over time and has not been used to study a college live mascot program. Although a decreasing campus tradition, college live mascots have a relationship and impact on a student’s experience and college identification, as well as university engagement with alumni and the public. Therefore, understanding how change is identified and experienced by campus stakeholders of a college live mascot program describe the various complexities and issues that initiate a climate for institutional change. To explain the evolution of a college live mascot program, oral histories across twenty years of campus stakeholders, including student trainers, campus administrators, and external consultants were analyzed using Kotter’s (1995) model. The findings of this study affirmed that the steps associated with Kotter’s (1995) change model, with a specific focus on the first three steps, are relevant for ad hoc changes, and offer implications for higher education change.